2005
DOI: 10.1074/jbc.m505630200
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Microdomain (“Glycosynapse 3”) Controls Phenotypic Conversion and Reversion of Bladder Cancer Cells through GM3-mediated Interaction of α3β1 Integrin with CD9

Abstract: Human bladder cancer cell lines KK47 (noninvasive and nonmetastatic) and YTS1 (highly invasive and metastatic), both derived from transitional bladder epithelia, are very similar in terms of integrin composition and levels of tetraspanin CD9. Tetraspanin CD82 is absent in both. The major difference is in the level of ganglioside GM3, which is several times higher in KK47 than in YTS1. We now report that the GM3 level reflects glycosynapse function as follows: (i) a stronger interaction of integrin ␣3 with CD9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 57 publications
7
106
0
Order By: Relevance
“…Thus, various cell adhesion processes mediated by GSLs and TSP cause extensive phenotypic changes, including reversion from malignant to normal cell phenotype (8,9,25). In analogy, Bissell and colleagues (26,27) showed that functional antibodies directed to ␤1 integrin of breast cancer cells caused reversion, in vitro and in vivo, to normal cellular organization, indicating that malignancy may arise from disorganization of glycosynaptic microdomain rather than from changes in gene structure and expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, various cell adhesion processes mediated by GSLs and TSP cause extensive phenotypic changes, including reversion from malignant to normal cell phenotype (8,9,25). In analogy, Bissell and colleagues (26,27) showed that functional antibodies directed to ␤1 integrin of breast cancer cells caused reversion, in vitro and in vivo, to normal cellular organization, indicating that malignancy may arise from disorganization of glycosynaptic microdomain rather than from changes in gene structure and expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were grown in six-well culture plates to Ϸ90% confluence, washed, incubated overnight with GSL/nanosphere suspension, washed with PBS containing 1 mM sodium vanadate, and lysed, and levels of P-Src (Tyr-416) or P-p44/42 MAPK (Thr-202/Tyr-204) were measured as described in ref. 8. Blocking effect of mAb 8E11 on p-Src or p-MAPK signaling inhibition by GM2/GM3-coated nanospheres was determined by incubation of HCV29 cells overnight at 37°C with 5% CO 2 and 1 ml of serum-free RPMI medium 1640, containing GM2/GM3-coated silica nanospheres preincubated, as above, with mouse IgG (1 g/ml) or mAb 8E11 (IgG3) (1 g/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound, originally found as a minor component of A431 cells displayed a much stronger inhibitory effect than GM3 on EGFR tyrosine kinase in vitro in isolated membranes, although lyso-GM3 displayed strong cytotoxicity. Lyso-GM3 dimer showed inhibitory effect similar to that of lyso-GM3 but had no cytotoxic effect [18]. Therefore, lyso-GM3 dimer, or its mimetics, are interesting candidates for tumor growth suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosphingolipids, including gangliosides, have the novel capability to interact with many functional membrane proteins, such as cytoplasmic signal transducers (Src family kinases, small G-proteins) [13,14], tetraspanins (CD9, CD81, CD82) [15][16][17][18], adhesion receptors (integrins) [19,20], and growth factor receptors [1,[21][22][23]. Studies on modulatory effects, initially observed with GM3 on EGFR tyrosine kinase [1], have been extended to effects of GM1, GD1a, GD1b, and GT1b on platelet-derived growth factor receptor [21,24], GM1 and plasmalopsychosine on nerve growth factor receptor [23,25], and GM3 and sialyl-nLc4 on insulin receptors [22,26].…”
Section: Discussionmentioning
confidence: 99%